RELATIONSHIP WARM WATER COMPRESS COMPLEMENTARY THERAPY TO MENSTRUAL PAIN IN ADOLESCENT FEMALES AT SMAN 4 - Rini Hariani Ratih; Sinta Mustika Sari; Dewi Sartika Siagian (LPPM Universitas Abdurrab, 2025)
Introduction Dysmenorrhea which is often known as menstrual pain is a painful cramping sensation in the lower abdomen, dysmenorrhea can have a negative impact on a woman's daily life, this condition often causes high levels of absenteeism at school and reduces participation in various activities. Objective To determine the relationship of warm compress therapy to the level of menstrual pain in adolescents at SMAN 4 Pekanbaru. Method Quantitative research type Quasi experimental research design (one group pretest-posttest design). The population in this study was 340, with a purposive sampling technique totaling 153 female students. Results Before being given warm compress treatment, the majority of respondents experienced menstrual pain on a moderate pain scale of 87 respondents and a minority of respondents on a severe pain scale of 27 respondents. After being given warm compress treatment, the majority of respondents experienced menstrual pain on a mild pain scale of 79 respondents and a minority of respondents on a severe pain scale of 9 respondents and 35 respondents did not feel dysmenorrhea pain. Conclusion There is a relationship between complementary therapy of warm water compresses and reducing menstrual pain in female adolescents at SMAN 4 Pekanbaru. Keywords: Menstrual pain, Warm water compress, Adolescent girls